2016
DOI: 10.3390/ijerph13111045
|View full text |Cite
|
Sign up to set email alerts
|

DALY-Based Health Risk Assessment of Construction Noise in Beijing, China

Abstract: Noise produced by construction activities has become the second most serious acoustic polluting element in China. To provide industry practitioners with a better understanding of the health risks of construction noise and to aid in creating environmentally friendly construction plans during early construction stages, we developed a quantitative model to assess the health impairment risks (HIA) associated with construction noise for individuals living adjacent to construction sites. This model classifies noise-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 65 publications
0
22
0
Order By: Relevance
“…Another study was identified from the recent Internoise 2019 conference [52] giving a total of 34 studies for consideration. Ten studies were excluded as they did not directly measure noise [20,21,[24][25][26][27]35,37], or because no associations between noise exposure and mental health were reported in the paper [29,32] (see Appendix A.2). This left 24 studies for inclusion in the review.…”
Section: Grade Evaluationmentioning
confidence: 99%
“…Another study was identified from the recent Internoise 2019 conference [52] giving a total of 34 studies for consideration. Ten studies were excluded as they did not directly measure noise [20,21,[24][25][26][27]35,37], or because no associations between noise exposure and mental health were reported in the paper [29,32] (see Appendix A.2). This left 24 studies for inclusion in the review.…”
Section: Grade Evaluationmentioning
confidence: 99%
“…It also provided evidence that the impact of construction activities on noise complaints may be stronger during after-hours than regular hours. These results imply that the existing noise by-laws may not be effective in restricting construction activities at night and during sleeping hours, which were found to have harmful effects on sleep quality and related health effects (Halperin, 2014;Hammer et al, 2013;Hume, 2010;Xiao et al, 2016;Zou et al, 2007). Although construction activities can be considered as a sign of a healthy economy (Garcia-Milà and McGuire, 1992;Glaeser et al, 2006) Figure 2.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, this study provides evidence that construction noise has far reaching impacts on the general population that go beyond those experienced by workers in occupational settings. In the (Fernández et al, 2009;Golmohammadi et al, 2013;Lee et al, 2015;Li et al, 2016;Neitzel et al, 2011;Seixas et al, 2012;Xiao et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, our findings suggest that vicinal construction noise was the most significant noise among elderly individuals in our study. In China, 42.1% of environmental complaints have been reported to be associated with noise, 64.4%, 25.0%, 7.4%, and 2.2% of which were attributed to neighborhood noise, construction noise, industrial noise, and traffic noise, respectively; thus, noise is becoming a more serious problem due to rapid urbanization throughout China [ 31 ]. In our study, regarding environmental noise annoyance, the highest proportion of participants responded with construction noise, followed by aircraft, automobile, and neighborhood noise.…”
Section: Discussionmentioning
confidence: 99%